2020
DOI: 10.1002/ehf2.12614
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between B‐type natriuretic peptide and invasive haemodynamics in patients with severe aortic valve stenosis

Abstract: AimsIn patients with aortic stenosis (AS), B-type natriuretic peptide (BNP) is a prognostic marker. However, there is little information on the association between BNP and invasive haemodynamics in AS. The aim of the present study was to assess the hitherto not well-defined relationship between BNP and invasive haemodynamics in patients with severe AS undergoing aortic valve replacement (AVR) with a view to understand the link between high BNP and poor prognosis in these patients. In particular, we were intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
(52 reference statements)
2
9
0
1
Order By: Relevance
“…Evidence exists that enhanced BNP is a marker of the presence of CpcPH in patients with severe aortic stenosis. 24 LFT parameters and PH prediction have also been reported in the literature. An interesting study of 105 patients with idiopathic pulmonary fibrosis (IPF) revealed that the ratios FVC/DLCO (forced vital capacity/diffusion capacity) and diameters of pulmonary artery/aorta were useful adjuncts to sPAP to predict PH in a linear regression model (R 2 ¼0.39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence exists that enhanced BNP is a marker of the presence of CpcPH in patients with severe aortic stenosis. 24 LFT parameters and PH prediction have also been reported in the literature. An interesting study of 105 patients with idiopathic pulmonary fibrosis (IPF) revealed that the ratios FVC/DLCO (forced vital capacity/diffusion capacity) and diameters of pulmonary artery/aorta were useful adjuncts to sPAP to predict PH in a linear regression model (R 2 ¼0.39).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists that enhanced BNP is a marker of the presence of CpcPH in patients with severe aortic stenosis. 24…”
Section: Discussionmentioning
confidence: 99%
“…Despite different sPAP cut-off values, significantly higher plasma concentrations were detected for both NT-proBNP and GDF-15 in the "PH group" in comparison to the "non-PH group", consistent with the results of our study. In a publication of 252 patients with severe AS and invasively measured right heart catheterization data to determine PH, Maeder et al [30] described that BNP or its biologically inactive signal peptide NT-proBNP is indicative for the presence of PH at higher plasma concentrations. Again, it must be emphasized that a large proportion of PH patients have atrial fibrillation (46.4%) and mitral valve insufficiency ≥II°(33.0%) as a potential "confounding factor" in the current cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A waiver of consent was granted. We have previously reported on other aspects of the hemodynamics in this population [11][12][13][14][15][16][17].…”
Section: Study Populationmentioning
confidence: 81%